Analysis of Factors Affecting Income Distribution Inequality in Indonesia 2009-2013 Period - Enny Istanti; Bramastyo Kusumo Negoro; Achmad Daengs GS (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: to analyze the effect of population, minimum wages and unemployment on inequality of income distribution in Indonesia. This study uses secondary data in the form of panel data consisting of time crosses for the period 2009-2013 and cross places in 33 provinces in Indonesia Design/methodology/approach: The analysis carried out is a quantitative analysis using multiple linear regression to answer the problem formulation and determine the effect of predetermined variables. Findings: All independent variables are said to have a joint (simultaneous) influence on the dependent variable because it is seen from the level of significance that the number is 0.002 less than 0.05, which means that there is a significant effect simultaneously between the population, minimum wages and unemployment on inequality of income distribution. in Indonesia the period 2009-2013. There is a partially significant effect between the minimum wage and the inequality of income distribution. The minimum wage variable has a dominant influence on inequality in income distribution in Indonesia for the 2009-2013 period. Practical implications: To Intensify business in the economic sector in order to touch the lower class of society Originality/value: This paper is original Paper type: Research paper